Changes in snowfall/precipitation-day ratio in Slovakia and their linkages with air temperature and precipitation - NIKOLOVA, Nina; FAŠKO, Pavol; LAPIN, Milan; ŠVEC, Marek (Contributions to Geophysics and Geodesy, 2013)
Knowledge on snowfall and precipitation variability is one of the most important information about climate changes. The presented study is based on daily data for precipitation totals and new snow cover depths and monthly air temperature from 29 meteorological stations in Slovakia. The aim is to determine to what extent the change of monthly air temperature mean affects the snowfall in the mountainous area of Slovakia. In order to achieve the aim of the research work, the snow days and precipitation days (SD/PD) ratio is calculated for the months from October to April and the trend is investigated. On the basis of correlation analysis it is determined that the main factor for changes in the SD/PD ratio is the mean monthly air temperature while precipitation plays an important role only for the stations with the altitude above 1300 m. Spatial distribution of the changes in the SD/PD ratio for the winter time (December – January – February) during the period 1981–2011 was investigated by cluster analyses. The results show that the stations are grouped according to their geographical location and relief of the territory.